Rodolf Sirera i la renovació del teatre català - Carbó, Ferran (Caplletra. Revista Internacional de Filologia, 2015)
The present article begins with a revision of theatrical development in País Valencià during the post-war period, and goes on to focus on the most important writer, Rodolf Sirera, whose production is presented organised in different moments. It finally offers an analysis of the text El verí del teatre as an example of the maturity and transgression of his dramatic discourse.